PHARMACOTHERAPY OF NON-SMALL CELL LUNG CANCER: A SHORT REVIEW - O, Balaji (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Lung cancer is a global health problem with non-small cell lung cancer (NSCLC) being the most common histopathological variant causing almost 28% deaths in the United States of America. Platinum compounds were the mainstay of treatment, and since past 10 years, various newer targeted therapies have come into play. Epidermal growth factor receptor and anaplastic lymphoma kinase mutations play a major role in the development of advanced disease. Hence, targeted therapies and immunotherapies will remain an integral part in the management of advanced disease. Hence, this review focuses on the newer drugs approved by Food and Drug Administration to treat NSCLC